Management front end for cache server - Chan, Yunn Chyuan (2010)
Caching and proxy technology designed to solve the internet issues in organization include security and performance by cache and filter, the request between network with another network mostly internal LAN and global network. Squid cache server is one of the most famous cache server that running on multiple platform. Squid cache server use squid. conf file to store configuration and setting for the cache server.Whenever administrators want to configure the cache server, they need to interact with the ifie itse1f, which require administrator to study and memories a lot of the commands.Administrators also need extra knowledge on how to set up the server to run at platform.SQ Squid cache server management front end is design to overcome this inconvenient by providing graphical user interlace design to interact with the squid. conf file on behalf of the administrators. All options available for Squid cache server is configure using GUI make it easier to understand and configure. However, SQ Squid cache server management front end is not a new cache server; it's only a graphical user interface management front end for existing cache server-Squid cache server. 'SQ Squid Management front end help administrators understand and configure the Squid cache server where extra knowledge on command use in Squid cache server is not needed but only knowledge on cache, network, and security.